Characterisation of key volatile compounds in fermented sour meat after fungi growth inhibition. (1st August 2022) - Zhong, Aiai; Chen, Wei; Hu, Lin; Wu, Zhongqin; Xiao, Yu; Li, Ke; Li, Zongjun; Wang, Yuanliang; Wang, Chuanhua
Abstract: The objective of this study was to explore the effect of fungi on volatiles in sour meat. Here, we investigated the microbial community composition in meat after 80 days of fermentation and concluded that Lactobacillus, Debaryomyces, Pichia, and Wickerhamomyces were the dominant microorganisms in the sour meat. The inhibition of fungi in the sour meat by natamycin reduced the number of volatiles from 74 to 60. Esters, alcohols, aldehydes, ketones, and hydrocarbons were significantly lower in antibiotic-treated group (Group B) than in control group (Group A). The relative odor activity value (ROAV) showed that decanal, 1-octen-3-ol, ethyl heptanoate, and nonanal contributed to the flavor of the sour meat in both groups, and their relative content and contribution were significantly higher in Group A than in Group B, indicating that natamycin attenuated the contribution of these substances to the flavor of the sour meat. Finally, multivariate data analysis was performed to obtain 21 volatiles (variables important in the projection [VIP] > 1) that caused differences in the meat flavor between the two groups. The study provides a theoretical basis for future research on mechanisms of flavor formation in fermented products from a microbial perspective. Highlights: High-throughput sequencing technology to analyze microbial diversity in sour meat. SPME-GC-MS combined with ROAV screened for 20 key volatile compounds. 21 differential volatile flavor compounds obtained based on VIP >1.0 Fungi play an important role in the formation of volatiles in sour meat.